Back to Eudaimonia as a Social Relation: What Does the Covid Crisis Teach Us about Individualism and its Limits? - Goffi, Emmanuel Roberto (Conatus - Journal of Philosophy, 2022)
The current health crisis that has spread worldwide has raised many questions regarding our relations to the Other and to ourselves. Through isolating people, Covid-19 has demonstrated the need we face, as human beings, to socialize and to get in contact, physically speaking, with others. As Aristotle stated, human beings are political animals, meaning social animals that can flourish only in the polis through the process of interacting with each other in quest of eudaimonia, i.e. happiness. Along with the rise of socio-physical distancing imposed due to the pandemic, people around the world have experienced isolation and the lack of human contact and interaction. In the Western world this isolation has led to an increase in mental health issues, and this fact has to be taken into consideration by the government when making decisions regarding the reinforcement or the slackening of measures in the context of Covid. The pandemic has shed a light on the limits of individualism as it has developed in some places. The quest for happiness has slowly led some societies to create a kind of a solipsistic world in which there would exist no reality, no truth outside individuals’ perceptions. Consequently, each human being is considered as “the measure of all things,” as Protagoras noted. This unique experience could then give us the grounds to question our relations to each other, to investigate our understanding of eudaimonia, and to revisit what it means to live in a society.